The role of specific subjects in education production functions: Evidence from morning classes in Chicago Public High Schools - Kalena E. Cortes; Jesse Bricker; Chris Rohlfs (Institute for the Study of Labor (IZA), 2010)
Absences in Chicago Public High Schools are 3-7 days per year higher in first period than at other times of the day. This study exploits this empirical regularity and the essentially random variation between students in the ordering of classes over the day to measure how the returns to classroom learning vary by course subject, and how much attendance in one class spills over into learning in other subjects. We find that having a class in first period reduces grades in that course and has little effect on long-term grades or grades in related subjects. We also find moderately-sized negative effects of having a class in first period on test scores in that subject and in related subjects, particularly for math classes.
Keywords: I20; I21; J13; 330; Education production; subject-specific; math; English; morning classes; first period; course schedule; quasi-experimental; attendance; absenteeism; Chicago; high school; Bildungsniveau; Allgemeinbildende Schule; Bildungsverhalten; Fehlzeit; Bildungsökonomik; Schätzung; Chicago (Ill.)